Comparative Analysis on Service Quality &Customer Satisfaction: Empirical Evidence from Pakistan Hotel Industry - SYED NASEEB ULLAH SHAH; DR. QADAR BAKHSH BALOCH (Journal of Business & Tourism, 2021)
The phenomenon of Quality of service, as the degree of excellence at an acceptable price, has gained a pivotal place in the success or failure of a business or gaining and maintaining customer satisfaction over the years. The research study aimedto compare the mean score of KPK, Punjab and Islamabad hotel customer’s mean score and to recommend strategies for improving managerial efficiency and operational effectiveness in improvising and sustaining service quality so as to gain and sustain customer satisfaction and brand loyalty. The population included hotels having restaurants and living accommodation both, and stratified on the bases of geography located in selected cities of Khyber Pakhtunkhwa, Islamabad and Lahore. The sample of hotel , worked out on the bases of 10hotels from each location and 20 customers from each hotel, comprises of 60 hotels and 1200 customers from Khyber Pakhtunkhwa, and 20 hotels and 400 customers forum Islamabad and Lahore . The paired samples t-test used to compare the mean score difference about the customers of KPK, Punjab and Islamabad Pakistan found that there is significance difference between the mean score of Punjab and KPK customers on service quality attributes. The mean score of Punjab customers is and Islamabad customers are found that there is significance difference between the mean score for Punjab and customers on service quality attributes. The research contributes theoretically and practically to the Hotel service industry and customer satisfaction in Pakistan which is supported by the empirical evidence and would help the Pakistan’s Hotel industry to improve its business performance through improving their service quality and adding in to their customer satisfaction.